An analysis and critique of the BIS proposal on capital adequacy and ratings - Altman, Edward I; Saunders, Anthony (Journal of Banking & Finance, 2001)
This paper examines two specific aspects of stage 1 of the Bank for International Settlement’s (BIS’s) proposed reforms to the 8% risk-based capital ratio. We argue that relying on “traditional” agency ratings could produce cyclically lagging rather leading capital requirements, resulting in an enhanced rather than reduced degree of instability in the banking and financial system. Despite this possible shortcoming, we believe that sensible risk based weighting of capital requirements is a step in the right direction. The current risk based bucketing proposal, which is tied to external agency ratings, or possibly to internal bank ratings, however, lacks a sufficient degree of granularity. In particular, lumping A and BBB (investment grade corporate borrowers) together with BB and B (below investment grade borrowers) severely misprices risk within that bucket and calls, at a minimum, for that bucket to be split into two. We examine the default loss experience on corporate bonds for the period 1981–1999 and propose a revised weighting system which more closely resembles the actual loss experience on credit assets.